A framework for inland cities to prevent marine debris: A case study from Durham, North Carolina - Lauer, Nancy E.; Nowlin, Michelle B. (Frontiers in Marine Science, 2022)
Land-based sources of litter are increasingly recognized as significant contributors to marine debris, and rivers can carry debris to the coast from far-inland sources. In this paper, we demonstrate the important role inland cities can play in the marine debris crisis by reducing their own marine debris contributions. Given this role, we provide a framework for inland cities to prevent plastic pollution along with the lessons learned from introducing these strategies in Durham, North Carolina, a mid-sized, inland city that drains to the ocean through the Cape Fear and Neuse River watersheds. This framework guides city officials, resource managers, and community partners on how to characterize the plastic pollution problem in their city by collecting baseline data on plastic waste and litter. This framework also provides practical and equitable solutions for inland cities to address plastic pollution. We recommend that inland cities prioritize policy solutions that reduce waste at the source – to the extent that their state constitutions allow – and to also use authorities for stormwater controls to capture and remove debris as long as litter persists. Replicating this framework in other inland cities opens vast opportunities to manage and reduce marine debris from an often-overlooked source.